Assessment of uveal melanomas using advanced diffusion-weighted imaging techniques: value of reduced field of view DWI ("zoomed DWI") and readout-segmented DWI (RESOLVE). (August 2019) - Seeger, Achim; Batra, Marion; Süsskind, Daniela; Ernemann, Ulrike; Hauser, Till-Karsten
Background: Diffusion-weighted imaging (DWI) has become an important tool for lesion characterization. Advanced techniques of DWI may be used to improve image quality. Purpose: To evaluate multi-shot segmented DWI (rs-EPI, RESOLVE) and reduced field-of view DWI (rFOV-EPI, "zoomed" EPI) in patients with ocular melanoma and to compare image quality and diagnostic performance in differentiation of melanoma from retinal detachment. Material and Methods: In this prospective and IRB-approved trial, we examined 26 patients using methods including conventional single-shot echo-planar DWI (ss-EPI), rs-EPI, and rFOV-EPI. Subjective image quality was compared using a four-point score and the maximum tumor length was measured in all sequences. Apparent diffusion coefficient (ADC) measurements were performed using a region-of interest analysis. Tumor delineation and differences in ADC values between melanomas and retinal detachments were compared. Results: Diffusion restriction was markedly reduced in melanomas in all applied image techniques. Subjective image quality was significantly higher for rFOV-EPI (score = 3.5 ± 0.5) compared with rs-EPI (score = 3.3 ± 0.6) and ss-EPI (score = 2.5 ± 0.9). Regarding tumor diameter measurements, rFOV-EPI showed the best agreement compared with high-resolution conventional sequences. ADC measurements of the tumor and retinal detachment differed significantly ( P  < 0.001) with the rFOV-EPI performing best (sensitivities and specificities compared with T1-weighted ss-EPI 61%/82%; rFOV-EPI 86%/92%; rs-EPI 79%/92%, respectively). Conclusion: rFOV-EPI showed improved image quality compared with ss-EPI and rs-EPI, the most accurate tumor delineation and the best differentiation from retinal detachments in our patients.